Continuous negative-to-positive tuning of thermal expansion achieved by controlled gas sorption in porous coordination frameworks - Josie E. Auckett (Nature Portfolio, 2018)
Achieving control over the thermomechanical properties of functional materials is desirable, yet remains highly challenging. Here, the authors demonstrate continuous negative-to-positive tuning of thermal expansion in two Prussian blue analogues, by varying the concentration of adsorbed CO2.